2022
DOI: 10.24251/hicss.2022.088
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Interactions of Augmented Reality Solutions

Abstract: The rapid evolution of augmented reality has resulted in an ever-increasing number of applications in a wide range of industries and services. Despite this progress, there is still a lack of conceptual understanding of AR interactions and the entire solution space. To bridge this gap, we conceptualize AR solution interactions and provide a comprehensive taxonomy. To represent the state-of-the-art, we build upon an extensive literature review. The resulting taxonomy consists of seven dimensions that encompass 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, viewing AR through mobile device screens is not as immersive and interactive (Holdack et al, 2022). ARSG are a new technology that incorporates a screen or projection system that displays digital information in the user's field of view (Bräker & Semmann, 2023). The glasses use sensors and cameras to track the movement of the wearer and the environment around them, creating a digital extension of the real world.…”
Section: The Affordances Of Augmented Reality and Arsgmentioning
confidence: 99%
“…However, viewing AR through mobile device screens is not as immersive and interactive (Holdack et al, 2022). ARSG are a new technology that incorporates a screen or projection system that displays digital information in the user's field of view (Bräker & Semmann, 2023). The glasses use sensors and cameras to track the movement of the wearer and the environment around them, creating a digital extension of the real world.…”
Section: The Affordances Of Augmented Reality and Arsgmentioning
confidence: 99%
“…Thus, the current prototype could be extended to let users customize their view, switch on and off data layers or save the position of discovered obstacles. As a preliminary work, we already aimed to classify AR interactions (Bräker et al, 2022;. The following steps would be investigating use cases and appropriate interaction techniques accordingly.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%
“…In organizational contexts, research concentrates, for example, on AR use in technical services (Niemöller et al, 2019), infrastructure services (Osterbrink et al, 2021), logistics (Rauschnabel & Ro, 2016), and healthcare (Klinker et al, 2019). Other research systematizes interactions within AR (Bräker et al, 2022;Hertel et al, 2021). Conceptualizations that seek to explore a multitude of aspects related to AR, its use and applicability, and niche aspects like privacy (Rauschnabel et al, 2018) can also be found.…”
Section: Introductionmentioning
confidence: 99%